LINKING SENSORY PERCEPTION, PRODUCT PERCEIVED VALUE, AND ENVIRONMENTAL CONCERNS TO BEHAVIORAL INTENTION THROUGH SENSORY BRAND EXPERIENCE - Matondang, Seria Pita Dewi; Ruspitasari, Widi Dewi (Institut Teknologi dan Ilmu Sosial Khatulistiwa, 2025)
The purpose of this research is to explore the impact of sensory perceptions, the value of a product, and social awareness on consumers' behavioral intention to consume viral food in East Java. Conversely, this research also evaluated the effect of brand sensory experience as a mediation variable. This research was conducted using the qualitative method of an online questionnaire with 165 respondents from the Generation population. It was analyzed using Partial Least Squares-Structural Equation Modeling (PLS-SEM) to evaluate the relation between variables. This research showed that the value of a product and brand sensory experience is significantly related to consumers' behavioral intention. Besides, sensory perceptions do not directly relate to consumers' behavioral intentions. Instead, sensory perceptions have a significant impact on brand sensory experience. This result emphasizes the importance of a sensory experience-based marketing strategy and improving product quality to maintain consumer loyalty. For further research, it's suggested that the focus of the research be expanded to include various restaurant types and additional aspects, like social knowledge and relevant social norms.Keywords: Sensory Perceptions, Product Perceived Value, Environmental Concern, Sensory Brand Experience, Behavioral Intentions